NUCLEIC ACID AND PROTEIN-BASED NANOTHERAPEUTICS FOR PRECISION MEDICINE - Adwoa Agyemang; Samuel Bediako; Kwame Mensah (Yayasan Adra Karima Hubbi, 2026)
Nucleic acid and protein-based nanotherapeutics have emerged as revolutionary approaches in the field of precision medicine, offering highly targeted treatments for various diseases, including cancer, genetic disorders, and viral infections. Traditional therapies often face challenges such as off-target effects, limited bioavailability, and inadequate therapeutic outcomes. Nanotechnology, leveraging the unique properties of nucleic acids (DNA/RNA) and proteins encapsulated in nanomaterials, provides solutions to these limitations by enabling controlled drug release, targeted delivery, and enhanced therapeutic efficacy. This study explores the potential of nucleic acid and protein-based nanotherapeutics in precision medicine, focusing on their mechanisms, applications, and future prospects. The research employs in vitro and in vivo models to evaluate the delivery efficiency, biocompatibility, and therapeutic effectiveness of these nanotherapeutics. The results indicate that nucleic acid-based nanoparticles, such as siRNA and DNA, show significant efficacy in gene silencing and expression modulation, while protein-based nanocarriers demonstrate enhanced targeting of specific cells and tissues. In conclusion, nucleic acid and protein-based nanotherapeutics offer promising advances in precision medicine, providing a new paradigm for treating diseases with high specificity and reduced side effects.